Callus induction from leaf explant of Citrus hystrix - Mohd Zaki, Nor Ilya (2013)
Citrus hystrix belongs to the Rutaceae family and is one of the most important commercial crops based on its nutritional, medicinal and economic value. An experiment was conducted for callus induction from leaf explant of C.hystrix and to determine the best combination of 2,4-dichlorophenoxyacetic acid (2,4-D) and Kinetin (KIN) on the callus induction with six explants per treatment. This experiment was conducted using Randomized Complete Block Design (RCBD) with 15 treatments and 3 replications. Data were analyzed using the Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) was used for comparison between treatment means. There was significant difference on explant survival. The highest percentage of explant survival was 68% in T5 (2.0 mg/l KIN). Besides, there was no significant difference on explant producing callusbetween treatments. The highest mean percentage of explant producing calluswas in T5 (2.0mg/l KIN) which was 28% within 27 days of inoculation. T5 (2.0 mg/l KIN), T9 (3 mg/l 2,4-D + 1.5 mg/l KIN) and T15 (5 mg/l 2,4-D + 2.0 mg/l KIN) showed intensive callusing. It was found that T5 (2.0 mg/l KIN), T8 (3 mg/l 2,4-D + 1.0 mg/l KIN) and T10 (3 mg/l 2,4-D + 2.0 mg/l KIN) were likely to become embryogenic due to the presence of nodular structure. Thus, further studies need to be conducted to obtain the best combination of hormones on callus induction from leaf explant of C.hystrix employing short incubation period, producing high intensity of callusing and the ability to form embryogenic callus.